2016
DOI: 10.1038/srep27174
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of sulfated glycans in cancer cell adhesion and migration through use of branched peptide probe

Abstract: The tetra-branched peptide NT4 selectively binds to different human cancer cells and tissues. NT4 specifically binds to sulfated glycosaminoglycans on cancer cell membranes. Since sulfated glycosaminoglycans are involved in cancer cell interaction with the extracellular matrix, we evaluated the effect of NT4 on cancer cell adhesion and migration. We demonstrated here that the branched peptide NT4 binds sulfated glycosaminoglycans with high affinity and with preferential binding to heparan sulfate. NT4 inhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 48 publications
4
42
0
Order By: Relevance
“…Moreover, it was found that GAG binding was not a common characteristic of all galectins since Galectin-1 does not interact with GAGs [13]. Since sulfated GAGs are able to bind bioactive molecules involved in cell-cell and cell-ECM interactions [40], we could assume that the interplay and binding between Gal-3 and GalNAc containing GAGs might be the molecular basis that regulates several biological functions involved with cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that GAG binding was not a common characteristic of all galectins since Galectin-1 does not interact with GAGs [13]. Since sulfated GAGs are able to bind bioactive molecules involved in cell-cell and cell-ECM interactions [40], we could assume that the interplay and binding between Gal-3 and GalNAc containing GAGs might be the molecular basis that regulates several biological functions involved with cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…NT4 bound specifically with high affinity to membrane‐sulfated glycosaminoglycans (GAG) and to different membrane endocytic receptors belonging to the low‐density lipoprotein receptor family, including LRP1 and LRP6, all already known as potential druggable tumor markers involved in cancer biology . NT4 was much more selective than native monomeric analogues for binding to different human cancer cells and tissues .…”
Section: Branched Peptide Applicationsmentioning
confidence: 99%
“…Considering the role of sulfated GAGs in cancer cell interaction with the extracellular matrix, the effect of NT4 in cancer cell adhesion and migration was analyzed on different supports. NT4 inhibited adhesion and migration of different human cancer cell lines, strongly affecting the directionality of cell movement …”
Section: Branched Peptide Applicationsmentioning
confidence: 99%
“…The cancer selectivity of NT4 peptides is much higher than that of native monomeric neurotensin, which unlike NT4 does not discriminate between healthy human tissues and cancer [ 10 , 12 , 14 ]. We demonstrated that the branched structure gives NT4 the ability to bind sulfated glycosaminoglycan (GAG) chains of membrane heparan sulfate proteoglycans (HSPG), as well as different endocytic receptors of the low density lipoprotein receptor (LDLR) family, like LRP1 and LRP6 [ 16 , 17 ]. LDLR are already known to share many heparin-binding ligands with HSPG and both families include potential druggable tumor markers involved in cancer biology [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%